Soluble CD40 Ligand Levels in Children with Newly Diagnosed Graves' Disease - Kotb Abbass Metwalley; Hekma Saad Farghaly; Duaa Mohammed Raafat; Asmaa Mohammed Ismail; Ghada Mohamed Saied (Galenos Yayincilik, 2020)
Objective:Soluble CD40 ligand (sCD40L) is elevated in various autoimmune disorders, which may have diagnostic and therapeutic implications. The aims of the current study were to evaluate serum sCD40L concentrations in children with newly diagnosed Graves' disease (GD) and to correlate its levels with patients' clinical and laboratory parameters.Methods:This study included 48 children with newly diagnosed GD and 48 healthy children. Serum thyroid-stimulating hormone (TSH) (TSH, fT4 and fT3), TSH receptor antibodies (TRAbs), high sensitivity C-reactive protein (hsCRP) and sCD40L levels and thyroid volume were measured.Results:Compared to control subjects, children with GD had higher thyroid volume standard deviation scores (SDS) (p=0.001), and higher levels of hsCRP (p=0.001), TRAbs (p=0.001) and sCD40L (p=0.001). Significant correlations were found between sCD40L and age (p=0.01), thyroid volume SDS (p=0.001), hsCRP (p=0.01) and TRAbs (p=0.001). In multivariate analysis, sCD40L concentrations were correlated with TRAbs [odds ratio (OR)=3.1, 95% confidence intervals (CI): 2.2-2.7, p=0.001] and thyroid volume SDS (OR=2.1, 95% CI: 1.2-2.7, p=0.001).Conclusion:This preliminary study has evidence of high concentrations of sCD40L in children with newly diagnosed GD and a correlation between sCD40L and both TRAbs and thyroid volume, which may indicate a biologically active role for sCD40L in the pathogenesis of GD.